NutriTalk: Nutrition Intervention by Experts to Reduce the Impact of Stunting Through Mobile Based Applications Using Agile Method - Kurniasari, Arvita Agus; Olivia, Zora; Suryana, Arinda Lironika; Widiyawati, Agatha; Maria Rosiana, Nita (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
The prevalence of childhood stunting, a pervasive global health concern primarily attributed to persistent malnutrition, underscores an urgent need for intervention. In Indonesia, where stunting rates are alarmingly high, with approximately 27.6% of children under five affected, innovative solutions are imperative. This study introduces